2015
DOI: 10.1021/acs.jmedchem.5b00473
|View full text |Cite
|
Sign up to set email alerts
|

Differential Targeting of Human Topoisomerase II Isoforms with Small Molecules

Abstract: The TOP2 poison etoposide has been implicated in the generation of secondary malignancies during cancer treatment. Structural similarities between TOP2 isoforms challenge the rational design of isoform-specific poisons to further delineate these processes. Herein, we describe the synthesis and biological evaluation of a focused library of etoposide analogues, with the identification of two novel small molecules exhibiting TOP2B-dependent toxicity. Our findings pave the way toward studying isoform-specific cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…4, A and B), which express similar levels of both topoisomerase IIa and topoisomerase IIb (Padget et al, 2000), showed that pixantrone, mitoxantrone, and etoposide all increased topoisomerase IIa and topoisomerase IIb covalently bound to DNA. Consistent with these results, etoposide and mitoxantrone have been shown to target both topoisomerase IIa and topoisomerase IIb (Willmore et al, 1998;Errington et al, 2004;Mariani et al, 2015). An earlier study had suggested topoisomerase IIb as an important target for mitoxantrone (Errington et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…4, A and B), which express similar levels of both topoisomerase IIa and topoisomerase IIb (Padget et al, 2000), showed that pixantrone, mitoxantrone, and etoposide all increased topoisomerase IIa and topoisomerase IIb covalently bound to DNA. Consistent with these results, etoposide and mitoxantrone have been shown to target both topoisomerase IIa and topoisomerase IIb (Willmore et al, 1998;Errington et al, 2004;Mariani et al, 2015). An earlier study had suggested topoisomerase IIb as an important target for mitoxantrone (Errington et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…It has also been suggested that targeting of topoisomerase IIb is responsible for induction of anticancer drug-induced secondary malignancies produced by topoisomerase II-targeted anticancer drugs Cowell et al, 2012). Development of drugs such as NK314 (Toyoda et al, 2008) and etoposide analogs (Mariani et al, 2015) that specifically target the topoisomerase IIa isoform to reduce topoisomerase IIb-mediated toxicity/carcinogenicity is being actively pursued (Vejpongsa and Yeh, 2014). Because preclinical studies with pixantrone showed little or no cardiotoxicity, this result suggested that pixantrone, unlike the anthracyclines, may be specifically targeting the topoisomerase IIa isoform.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optimal topoisomerase II poisons will maximize interactions with hTOPOIIα to inhibit proliferating cells and minimize hTOPOIIβ interactions to reduce side effects. With this goal in mind, others have identified etoposide analogues with different isoform specificities but have not determined the mechanism of specificity [45]. Our study functionally validates a key residue determining isoform specificity and is critical to the improvement of this widely administered drug class.…”
Section: Discussionmentioning
confidence: 88%
“…K562 cells (1x10 7 ) were washed with PBS and then treated with lysis buffer containing 50 mM Tris-HCl (pH 8.0), 150 mM NaCl, 1 mM phenylmethane sulfonyl fluoride, 1 mM aprotitin and 1% NP40 for 30 min at 4˚C. Following centrifugation at 11,000 x g for 20 min, the protein concentration of the supernatant was determined; equal amounts (30 µg) of protein were separated by 10% SDS-polyacrylamide gel electrophoresis and then electro-transferred onto nitrocellulose membranes in transfer buffer.…”
Section: Antitumor Effects In Vivomentioning
confidence: 99%
“…DNA topoisomerases are a class of enzymes involved in the regulation of DNA supercoiling. Topoisomerase overexpression has been linked to a number of human malignancies and is the target for numerous chemotherapeutic agents (7). In the event that topoisomerases are blocked, the cell encounters problems during transcription of the DNA and during cell division.…”
Section: Introductionmentioning
confidence: 99%